Variation in Coronary Artery Disease Pattern and Risk Factors among Female Patients of Dierent Age Groups in Bangladesh - Islam, Shitil Ibna; Amin, Md Nurul; Nasrin, Sahela; Cader, F Aaysha (Ibrahim Cardiac Medical Journal, 2020)
Background & objective: Coronary Artery Disease (CAD) is a devastating life-threatening condition which varies with respect to age and sex. In Bangladesh a large number of patients currently undergoes coronary angiography for a variety of indications. Due to physiological changes after menopause, the females are more prone to develop CAD. So, the risk factors and pattern of CAD in female are subject change with changing ages. The objective of this study was to compare the risk factors and pattern of CAD in female patients of different age groups. Methods: This cross-sectional analytical study was conducted at Ibrahim Cardiac Hospital & Research Institute (ICHRI), Dhaka, Bangladesh between September 2005 to August 2016. All female patients (n = 7,627) who underwent coronary angiography during the period were included. They were identified from ICHRI dedicated Cath-lab Database. The patients were divided into three groups based on their age (Group-I ≤45 years, Group-II from age 46 to age 60 and Group-III from age 60 years onwards). A stenosis of ≥ 70% in any of the three major coronary arteries like Left Anterior Descending (LAD), Right Coronary Artery (RCA) and Left Circumflex Artery (LCX) was considered as significant stenosis, while a stenosis of ≥ 50% in left main stem (LMS) was considered significant for left main disease. The data pertaining to their risk factors and angiographic profile were compared among the three age groups to find the association of risk factors and angiographic pattern of the CAD at different age groups. Result: All the risk factors (diabetes, hypertension, dyslipidaemia and CKD) demonstrated their significant presence in Group II and III compared to those in Group I, while they were almost identical between Group II and III. More than 40% of the patients were overweight in all age groups and around 20% were obese including a negligible proportion with morbid obesity. ST-segment elevation MI, NSTEMI (Non-ST-elevation myocardial infarction), prior MI (Myocardial infarction), and ALVF (Acute left ventricular failure) were significantly higher in Group III than the two other groups had. However, unstable angina was significantly higher in age-group I & II and atypical chest pain in Group I. Incidence of Single vessel disease (SVD) was considerably higher in group II. Double vessel diseases DVD), Triple vessel disease (TVD), LM disease was significantly higher in group III compared to two other groups. Normal CAG (Coronary angiography) finding was higher among group I, although it was not significantly different from other two groups. Conclusion: The study concluded that the prevalence of conventional risk factors including overweight/obesity is almost similar between middle-aged and elderly women, while they are significantly lower in early middle-aged group. The elderly women usually present with STEMI (ST-elevation myocardial infarction), non-STEMI, stable CAD, ALVF, while middle-aged women commonly present with UA (Unstable Angina) and early middle-aged women with atypical chest pain. Severe CAD including and LM disease is relatively common in elderly women than those in their early middle-aged and middle-aged cohorts. Coronary artery disease advances with advancing age. Health-care providers should not underestimate the cardiac health of women. Ibrahim Card Med J 2019; 9 (1&2): 60-66